ETIOLOGICAL PROFILE OF MECHANICAL GASTRIC OUTLET OBSTRUCTION IN A TERTIARY CARE CENTER IN NORTH WEST INDIA - Dhiraj Saini; Akash Rajender; Himaxi Rathod; Pranav Mehta; Rajat Bhargava; Subash Nepalia; Sumit Yadav; Himaxi Rathod (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Gastric outlet obstruction (GOO) is defined as a mechanical impediment to gastric emptying, secondary to complete or partial obstruction of distal stomach, pylorus or proximal duodenum. In contrast to 1970s, when benign diseases were mainly responsible for GOO, malignancy has been the most common cause in recent decades. But there is little data regarding any change over last decade in etiological spectrum of GOO. We therefore conducted this study to find out current trends in etiological spectrum of GOO in India especially in our region.Methods: A prospective study of GOO cases from January 2022 to December 2023 was done. Patients in whom a senior gastroenterologist was unable to negotiate the standard Gastroscope across pylorus into distal duodenum due to mechanical impediment were considered to have GOO. The data analyzed included age, gender, endoscopic findings and histopathology reports.Results: Total 84 patients were included with mean age of 57.71±7.3 years. 63 of the 84 (75.0%) patients were male, with male to female ratio of 3.0:1.0 Etiology of GOO was malignant in 51 (60.71%) while benign in 33 (39.2%). Gastric malignancy was most common cause of malignant GOO while duodenal ulcer was most common cause of benign GOO. Conclusion: The etiology of GOO in north west India predominantly malignant (60.71%) but significant percentages (39.2%) also have benign causes. Overall gastric malignancy (39.2%) was the most common followed by peptic ulcer disease (29.7%). Males were more commonly affected with GOO than females.